The Relationship Between Tooth Brushing Behavior of Elementary School Students with Dental Caries and Stunting - Applonia Leo Obi; Anthonius Radja Ratu (Poltekkes Kemenkes Kupang, 2024)
The oral cavity is the most important part, the main place for the reception of nutrients for the body. Oral and dental health status, food consumption, nutritional status, and overall well-being are interrelated. Poor nutrition in children is caused by an imbalance of nutrients, leading to a deficiency of energy and protein, which hampers their growth and development. Stunted children are more susceptible to dental caries due to changes in saliva. Reduced saliva volume decreases its buffering and cleaning abilities. This study aims to analyze the relationship between tooth tooth-brushing behavior of elementary school students and dental caries and stunting. This is an observational analytical study with a cross-sectional design. The sample was selected through purposive sampling with a maximum of 50 students from SD Baumata, Taebenu District, Kupang Regency. Data collection was done using questionnaires and caries examinations to determine the presence of caries in the oral cavity. Stunting was measured anthropometrically using the weight-for-height index. The chi-square test results showed a significant relationship between knowledge (p=0.035), attitude (p=0.039), and behavior (p=0.039) with caries. In contrast, the test for the relationship between knowledge (p=0.0002), attitude (p=0.000), and tooth brushing behavior (p=0.000) all showed a significant relationship with stunting. The conclusion is that there is a relationship between the knowledge, attitude, and behavior of students with caries and stunting. It is recommended to conduct further research on the relationship between diet, nutrient intake, and the incidence of caries and stunting.